DAMPAK MUTU PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN DI TANGGALTOEA COFFEE & ROASTERY - Dimas Aji Khoirul Anam; Ita Rifiani Permatasari (Bajang Institute, 2024)
Customer loyalty is shaped by various elements, such as the quality of service and trust. Tanggaltoea Coffee & Roastery is a popular café located in Pandaan. This research seeks to explore how service quality and trust impact customer loyalty at Tanggaltoea Coffee & Roastery. This study employed a quantitative approach. It utilized primary data collectedquestionnaires distributred to 100 respondenrts, selectted usingg purposife sample. The participants were repeat customers of Tanggaltoea Coffee & Roastery, having made more than two purchases. Data analysis was conducted through multiple regression techniques. The independent variables were service quality and trust, while the dependent variable was customer loyalty. The findings indicated that the quality of service impacted customer loyalty, while trust also played a role in fostering loyalty. Both service quality and trust were significant factors influencing customer loyalty at Tanggaltoea Coffee & Roastery. According to the research findings, it is evident that Tanggaltoea Coffee & Roastery should uphold customer trust, as this trust significantly impacts customer loyalty. Maintaining this trust is crucial for encouraging repeat purchases.